The mandacaru did not blossom: Positivist science at the service of drought control in 1877-1879 - Goncalves, Paulo Cesar [UNESP] (Fundaco Oswaldo Cruz, 2018)
The article surveys the scientific solutions proposed to address droughts in Brazil's semi-arid sertao and frames them within a historical context characterized by seientificism, which then governed Brazilian and Western intellectual thought. It investigates how men or science devised theories and practices regarding the regions nature and sertao society. From this perspective, the article examines the process by which the Semi-arid sertao was settled; droughts since the colonial period; the social political, and economic impact or the great drought of 1877-1879; debates WO projects related to the scourge of drought, and the construction of the discourse of drought as a regional and national problem.
Keywords: drought; science; provinces of Northern Brazil; migrants; Brazil